Aetiological Spectrum and Management Strategies of Obstructive Jaundice in a Tertiary Care Hospital - Iqbal, Mohammad Faruq; Hossain, S M Shakhwat; Chowdhury, Md Al Amin (Bangladesh Armed Forces Medical Journal, 2025)
Background: Obstructive jaundice is a common problem in surgical and gastro-enterological practice. Cause of obstruction is heterogeneous that includes both benign and malignant conditions. Management also varied according to pathology and level of obstruction. Objective: To identify the causes of obstructive jaundice and management techniques employed in those cases in Dhaka combined military hospital. Methods: This prospective observational study was carried out in the department of hepatobiliary and pancreatic surgery of Dhaka combined military hospital. Sample size of the study was 96. Entry of the various variables of the each clinical data were done and were analyzed by computer based program SPSS (Statistical Package for Social Science, version 25.0). Means of the continuous variables of the groups were compered by Independent sample t test and nominal variables were compered by Chi square test. Results: Mean age of the study population was 55.11 years. Mean age of malignant cases was about 10 years more than benign cases (60.19 years vs 51 years). Choledocholithiasis was the most common (42.7%) benign cause of obstructive jaundice, whereas periampullary carcinoma (12.5%), carcinoma head of pancreas (10.4%) and cholangiocarcinoma (10.4%) were three most common causes of malignant obstruction. Choledocholithiasis was managed mostly by ERCP (48.78%) and open surgery (39.02%). 100% cases of periampullary carcinoma were managed by curative surgery, whereas only 40% cases of carcinoma head of pancreas and 20% cases of cholangiocarcinoma were managed by curative surgery. Conclusion: Choledocholithiasis was the most common benign etiology that particularly inflicts in younger age group. Malignant etiology was causing obstruction in older age group. ERCP is the first line of management in choledocholithiasis.Curative surgery was almost always possible in case of periampullary carcinoma. Bangladesh Armed Forces Med J Vol 58 No (1) June 2025, pp 39-47